Bahasa Inggris sebagai Katalis Perubahan: Memberdayakan Mahasiswa Manajemen Indonesia untuk Mendorong Pertumbuhan Ekonomi Berkelanjutan - Bayu Ade Prabowo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This classroom action research aimed to explore an innovative approach to teaching English that specifically targets the development of communication skills required for implementing sustainable business strategies. The study was conducted at the Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia (STIEPARI) Semarang, involving 30 management students. The research employed a mixed-methods approach, collecting data through surveys, interviews, classroom observations, and English proficiency tests. The findings revealed that the innovative teaching method, which integrated sustainability concepts and focused on developing relevant business communication skills, effectively enhanced students' English competence and understanding of applying sustainability concepts in business. The increased English proficiency positively impacted students' comprehension and ability to implement sustainability principles in business contexts. The study concludes that integrating sustainability concepts into English language learning for business purposes is an effective strategy for developing management students' competencies as change agents in promoting sustainable business practices. Recommendations for future research include expanding the sample, conducting longitudinal studies, exploring teachers' perspectives, and collaborating between business management academics and English language experts.